Schindler's list - Keneally, Thomas; Speilberg, Steven 1947-; Molen, Gerald R.; Lustig, Branko; Zaillian, Steven (Universal City Studios, 1993)
The true story of Oskar Schindler, a member of the Nazi party, womanizer, and war profiteer, who saved the lives of more than 1,100 Jews during the Holocaust.